'But this is not geography…! of ontological circumcisions and writing feminist geographies from India. Issue 7 (2nd September 2019) - Datta, Anindita
Abstract: Feminist geography still remains at the margins of human geography in India. The space occupied by the subfield, the nature of research and the skepticism routinely encountered by feminist geographers 'doing gender' in India all point to this marginal status. Drawing upon detailed status reports, personal communications and everyday encounters with patriarchy in the academy, this essay uses an autobiographical lens to address the pervasiveness of misogyny and the politics of gendered parochial and caste-based gatekeeping to make sense of the peculiar but marked 'ontological circumcision' of feminist geographies in India. 'Coming out' as a feminist geographer and writing gender from such locations is political and should be read as a resistance to these caste-ridden, male dominated and inherently misogynistic contexts.